2021
DOI: 10.3389/fmicb.2021.633141
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Root Nodule-Associated Bacteria of Diverse Legumes Along an Elevation Gradient in the Kunlun Mountains, China

Abstract: Bacteria in root nodules of legumes play important roles in promoting plant growth. In this study, we investigated root nodule-associated bacteria isolated from leguminous plants along an elevation gradient on the northern slope of the Kunlun Mountains, China, using a cultivation approach. In total, 300 isolates were obtained from seven legume species within six ecological zones. Isolates were identified based on 16S rRNA gene phylogenetic analysis and potential rhizobia were further identified using a recA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The orders Rhizobiales and Pseudomonadales, which belong to the Proteobacteria phylum, were improved in apple-marigold intercropping system rhizosphere soils, as well as the order Bacillales ( Figure 2A ). These orders are mainly enriched in the rhizosphere and decompose organic matter to promote soil carbon and nitrogen cycles ( Zhou J. et al, 2020 ; Pang et al, 2021 ). Thus, their enrichment may improve soil nutrients and promote plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…The orders Rhizobiales and Pseudomonadales, which belong to the Proteobacteria phylum, were improved in apple-marigold intercropping system rhizosphere soils, as well as the order Bacillales ( Figure 2A ). These orders are mainly enriched in the rhizosphere and decompose organic matter to promote soil carbon and nitrogen cycles ( Zhou J. et al, 2020 ; Pang et al, 2021 ). Thus, their enrichment may improve soil nutrients and promote plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…To validate our hypothesis, the ecological niches of these endophytes, as reported earlier, were correlated with our data. Bacillus endophyticus was first reported as an endophyte of the cotton plant (Reva et al, 2002) and later found as an endophyte of several plants, including sugarcane (Pirhadi et al, 2018), cotton (Vinodkumar et al, 2018), onion (Ibrahim et al, 2020), mung bean, cowpea and soybean nodules (Bakhtiyarifar et al, 2021), Chinese mountain legumes (Pang et al, 2021), groundnut (Pal et al, 2021), medicinal plants like Salvadora persica (Moustafa et al, 2016), Vernonia anthelmintica (Rustamova et al, 2020), Gloriosa superba (Das et al, 2021) and halophyte Salicornia europaea (Zhao et al, 2016). This species was also isolated from wheat rhizosphere (Ibarra‐Villarreal et al, 2021; Verma et al, 2016), sugarcane rhizosphere (Mukhtar et al, 2017), rice phyllosphere (Devarajan Arun et al, 2020), termatorium soil (Chauhan et al, 2016), and honeydew of cotton whitefly (Roopa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, non-rhizobial endophytes and rhizoplane bacteria were mainly the genus Bacillus , unclassified Bacillales , Sphingomonas, Burkholderiaceae , which include known nitrogen-fixing bacteria [ 74 ], and Massilia, a major rhizosphere and root-colonizing bacteria of many plant species [ 75 ], in higher abundances during runner bean cultivation in summer along with Candidatus alysiosphaera , which was solely detected during the runner bean cultivation. Research has shown that both climate and host interactions may influence root nodule-associated bacteria isolated from leguminous plants [ 37 ]. Nevertheless, the rhizobia genera identified were the unclassified Burkholderiaceae, present in higher abundances during summer cultivation, yet the Rhizobiales spp.…”
Section: Discussionmentioning
confidence: 99%
“…The symbiotic relationships of leguminous crops with soil nitrogen-fixing bacteria [ 31 ] and other endophytic [ 32 , 33 ] and non-endophytic bacteria [ 34 , 35 , 36 , 37 ] have been extensively studied in the literature, given their contribution to agricultural sustainability and productivity [ 38 , 39 , 40 ] by initiating nutrient cycling in nutrient-depleted soils [ 41 ]. Agronomically important examples of nitrogen-fixing symbiosis in the Fabaceae family, include the common bean ( Phaseolus vulgaris L.) with Rhizobium etli , and lentils ( Lens culinaris Medik.)…”
Section: Introductionmentioning
confidence: 99%